Vocal mimicry in the song of Icterine warblers (Hippolais icterina): possible functions and sources of variability. Issue 5 (3rd September 2018) - Riegert, Jan; Jůzlová, Zuzana
Abstract : Vocal mimicry in birds is a well-known phenomenon, but in the majority of bird mimic species, its function, variability and accuracy still remain undiscovered. We analysed the song of 23 Icterine warbler ( Hippolais icterina ) males in České Budějovice (Czech Republic) and identified 52 mimicked species. Our results showed that Icterine warbler males (1) mimicked species that are present in their territories (i.e. passive sampling hypothesis), (2) mimicked alarm calls more frequently than non-alarm calls (i.e. alarm call hypothesis), (3) produced species-specific non-mimetic song that is most similar to the alarm calls of frequently mimicked species (i.e. acoustic similarity hypothesis) and (4) produced mimicry that is not perfect, but still acoustically convincing. These results suggest that Icterine warbler males largely reflect the surrounding acoustic environment in their song, but simultaneously selectively include vocalisations that are similar to their own song as a result of physiological constraints. We further found that (5) songs of neighbours are not more similar compared with more distant males and (6) there is no relationship between genetic and song similarity suggesting that song is learned mainly from heterospecifics.